Interesting overlooked findings in melanocytic nevi - José Cândido Caldeira Xavier-Júnior; Juliana Polizel Ocanha-Xavier; Deolino João Camilo-Júnior; Solange Correa Garcia Pires D'ávilla; Neivio José Mattar (BMC, 2019)
Abstract Since histological analysis is the gold standard for melanoma diagnose, to understand possible findings in nevi is the first step to avoid diagnostic errors. The aim of this paper is to describe several histological features that can be found in nevi and may be misunderstood or overlooked. Histological findings were organized into two groups: 1- adaptive findings (neurotization, sebaceous alteration, adipose metaplasia, amyloid deposition and calcifications, pseudovascular lacunae), 2- findings that can occasionally be associated with malignancy (suspicious for angiolymphatic invasion, perineural infiltration, deep mitosis, muscle infiltration). Each finding by itself does not mean that lesion is malignant. We have selected 13 cases of benign intradermal or compound melanocytic nevi excised for aesthetical purposes from our collection to illustrate possible overlooked findings in melanocytic nevi.